Relationship Between Physical Requirements Of Houses And Residential Density With The Incidence Of Pulmonary Tuberculosis On The Banks Of The Barito River - Azzahro, Mawaddah; Santoso, Imam; Rahmawati, Rahmawati; Juanda, Juanda (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Tuberculosis is an infectious disease and one of the world's 20 leading causes of death. Marabahan Health Centre for TB's working area consistently records the highest cases in the Barito Kuala district, with most of the population residing along the densely populated river. The study's goal was to determine the relationship between the physical requirements of the house, occupancy density, and the incidence of pulmonary tuberculosis on the banks of the Barito River. This research was an analytical observational study using a case-control method. The sample size in this study was 1:2, with 15 cases and 30 controls, for a total of 45 samples. The sampling technique used was purposive sampling. Statistical analysis used the chi-square test and the odds ratio test for risk factors. The results of the chi-square statistical test showed a relationship between the physical requirements of the house and the incidence of pulmonary tuberculosis in the Barito riverbanks, Barito Kuala Regency, in 2023. Results Odd's ratio analysis showed that the variable temperature is 20 times, the humidity is 13 times, the lighting is 18 times, and the occupancy density is 11 times the risk of developing pulmonary tuberculosis. People can get used to opening windows in the morning and not accumulate unused items in their rooms.